LONG-TERM GROWTH DYNAMICS OF EMERGING ECONOMIES IN LIGHT OF JÁNOSSY’S TRENDLINE THEORY - Soreg, Krisztina (PEOPLE: International Journal of Social Sciences, 2018)
It is a well-known fact – and the main research motivation of our paper – that at the turn of the 21st century our world economy witnessed an incipient fast development path produced by a group of emerging countries. Besides their enormous market size and raw material abundance, such countries as Brazil, Russia, India and China – known as the BRICs – have gradually become one of the most influential economic clubs of the world. Although it seemed that in the first years of the 2007-08 financial crises latter countries had been far from showing signs of downturn in contrast with some most developed economies, surprisingly, a moderate slowdown could be observed – with the exception of India – following 2014. In view of this, we are modelling the growth dynamics of the BRIC group as well as some Central Eastern European economies (CEECs) on the basis of Ferenc Jánossy’s trendline theory and aiming to detect some similar patterns in the stages of economic development of these countries. In the course of studying the long-term growth path of the BRIC country group our main research objective is to examine whether the economic growth of the most significant emerging countries might be modelled with the trendline theory of Jánossy and to analyze the post-transition growth as well as slowdown periods of the CEECs from the point of view of economic convergence. In order to identify some basic characteristics of the so-called middle-income trap episodes, as a selected methodology, we are applying chi-squared test as well as the analysis of variance (ANOVA).